Parenthood and risk preferences - Katja Görlitz; Marcus Tamm (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This study analyzes how risk attitudes change when individuals become parents using longitudinal data for a large and representative sample of individuals. The results show that men and women experience a considerable increase in risk aversion which already starts as early as two years before becoming a parent, is largest shortly after giving birth and disappears when the child becomes older. These findings show that parenthood leads to considerable changes in individual risk attitudes over time. Thus, analyses using risk preferences as the explanatory variable for economic outcomes should be careful in interpreting the findings as causal effects.
Keywords: D1; D81; J13; J16; 330; risk aversion; risk preferences; preference stability; parenthood; children; gender differences